Osteopetrosis: Report of a rare case - Nabikhan Ahmedkhan Athani; Mangala Parbhu Kakaraddi; Basawaraj N Kallalli; DNS V Ramesh (Wolters Kluwer Medknow Publications, 2012)
Osteopetrosis is a rare genetic disorder that causes generalized sclerosis of bone due to a defect in bone resorption and remodeling. Osteomyelitis is well documented as a complication of osteopetrosis. This disease can be severe and difficult to treat in the osteopetrotic patient. Prevalence is about 0.005% in general population. There are relatively few cases reported of osteopetrosis and its actual cause is not known. Dental abnormalities that present radiographically are delayed eruption and missing teeth. The overall clinical and radiographic findings of this patient were sufficient to arrive at the diagnosis of osteopetrosis.